Special education issues within the context of American society - Susan McLean Benner (Wadsworth Pub., 1998)
This text offers a current look at the field of special education and special education issues within the context of recent political and economic changes. It presents current issues from a unique perspective, looking back through history and comparing historical trends to today's social climate to show the impact on key issues in special education